CELL-MEDIATED AND HUMORAL IMMUNE-RESPONSES IN IMMUNIZED AND OR DERMATOBIA-HOMINIS INFESTED RABBITS - Lello, E.; Peracoli, MTS (Elsevier B.V., 1993)
The cell-mediated and humoral immune response of rabbits to antigens from larvae of Dermatobia hominis were analyzed by leucocyte migration inhibition factor assay (MIF), immunodiffusion (ID) and passive hemagglutination (PH) test in rabbits immunized with D. hominis extract, in rabbits immunized and infested with the parasite and rabbits infested with D. hominis. Twenty rabbits were divided into five groups: Group 1, rabbits immunized with a crude antigen extract, evaluated for 40 weeks at 4 week intervals; Group 2, rabbits immunized and infested with newly hatched larvae at 14 weeks post immunization (PI) and evaluated as Group 1; Group 3, rabbits immunized, evaluated for 28 weeks at 2 week intervals; Group 4, rabbits immunized and infested at 4 weeks PI and evaluated as Group 3; Group 5, rabbits infested and evaluated for 24 weeks at 2 week intervals. Different patterns of reactivity were observed in the infested and immunized animals: immunized rabbits developed antibodies and cellular immune responses earlier and at higher levels during immunization than the infested rabbits; the infestation at 14 weeks PI, when the cell-mediated and humoral immune response began to decrease, or at 4 weeks PI when these parameters were at higher levels, elicited an anamnestic response. After the spontaneous elimination of larvae by the host, from the 4th week PI onwards, high titers of antibodies and migration inhibition indices were maintained for a long period. These results suggest that the onset of cellular and humoral immune responses after immunization may be important as a biological control of myiasis and contribute to better understanding of the immune defense mechanism of the host against D. hominis.